Nursing practice facing depression in the elderly population - Brenda Roberta da Silva Pereira; Micaele Maria Silva de Lima; Cláudia Daniele Barros Leite Salgueiro; Valdirene Pereira da Silva Carvalho (Universidade de Pernambuco, 2019)
Objective: This study aimed to identify from an integrative literature review, nursing performance in the face of depression in the elderly, from 2014 to 2019.Methods:This is an integrative literature review, made through data collection in scientific articles in the LILACS, SCIELO and BDENF databases. Results: In the analysis of the results obtained, the selected journals discuss the importance of early detection of depression in the elderly, as it has been confused with normal symptoms of old age, further affecting the quality of life of these individuals. Also, the need for expressive gerontological care in the nurse's practice areas, which has a primary role as a health educator and due to his constant contact with the patient. Conclusion: It is concluded that the biopsychosocial vulnerability of elderly with depression is enhanced.